Currency risk management - Nina Dubiel; Klaudia Hilarowicz (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Effective risk management is becoming a key element of running a business, as an incorrect approach can lead to financial problems. In the global economy, companies use various strategies to reduce currency risk. The article analyzes currency risk in order to determine the most beneficial method of reducing the occurrence of this type of risk. The analysis was based on survey research. The study aimed to identify the most effective strategies and methods for minimizing currency risk and assess their impact on the financial result and competitiveness of economic entities. The results provided important information on currency risk management practices, which may be useful for further analysis and practical recommendations. The first part of the article discusses currency risk and risk management, and the next part discusses the research results.